Influence of Mn-doping concentration on the microstructure and magnetic properties of ZnO thin films - 吴兆丰 郭磊 程鲲 张峰 关荣锋 (Optoelectronics letters, 2016)
The microstructure and magnetic properties of Mn-doped ZnO films with various Mn contents,synthesized by magnetron sputtering at room temperature,are investigated in detail.X-ray diffraction（XRD） measurement results suggest that the doped Mn ions occupy the Zn sites successfully and do not change the crystal structure of the ZnO films.However,the microstructure of the Mn-doped ZnO films apparently changes with increasing the Mn concentration.Arrays of well-aligned nanoscale rods are found in the Mn-doped ZnO films with moderate Mn concentrations.Magnetic measurement results indicate that the ZnO films doped with moderate Mn concentration are ferromagnetic at room temperature.The possible origin of the ferromagnetism in our samples is also explored in detail.